Relationship between interactional quality, patients’ perceived value and patient satisfaction in military hospital - Azman Ismail; Ummu Ajirah Abdul Rauf; Nurshahira Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2025)
A systematic review of the military hospital literature indicates that interactional quality consists of three critical dimensions, namely responsiveness, assurance, and empathy. The competence of service providers, such as employees, to implement these quality dimensions can indirectly affect patient satisfaction through patients’ perceived value of the healthcare service system. This causal linkage has been extensively examined in both private and public healthcare systems; however, the mediating role of patients' perceived value is seldom highlighted in the military healthcare research literature. This gap has inspired the current study to investigate the association between interactional quality, patients' perceived value, and patient satisfaction. A cross-sectional data of 212 patients were gathered through purposive sampling at an established military hospital in Peninsular Malaysia. The measurement model and structural model were analyzed using SmartPLS. The findings of the structural equation modeling confirm that patients' perceived value does act as an essential mediating variable between interactional quality and patient satisfaction. This result supports the multi-dimensionality of perceived value and aids practitioners in developing customer assistance programs to maintain and improve the performance of military hospital services.